Helicobacter pylori Infection Increased Anti-dsDNA and Enhanced Lupus Severity in Symptomatic FcγRIIb-Deficient Lupus Mice - Surawut, Saowapha; Panpetch, Wimonrat; Makjaroen, Jiradej; Tangtanatakul, Pattarin; Thim-Uam, Arthid; Wongphoom, Jutamas; Tumwasorn, Somying; Leelahavanichkul, Asada (Frontiers in Microbiology, 2018)
The defect on Fc gamma receptor IIb (FcγRIIb), the only inhibitory FcγR, has been identified as one of the genetic factors increasing susceptibility to lupus. The prevalence of Helicobacter pylori (HP) and FcγRIIb dysfunction-polymorphisms are high among Asians, and their co-existence is possible. Unfortunately, the influence of HP against lupus progression in patients with lupus is still controversial. In this study, the interactions between these conditions were tested with HP infection in 24-wk-old FcγRIIb-/- mice (symptomatic lupus). HP induced failure to thrive, increased stomach bacterial burdens and stomach injury (histology and cytokines) in both wild-type and FcγRIIb-/- mice. While the severity of HP infection, as determined by these parameters, was not different between both strains, antibodies production (anti-HP, anti-dsDNA and serum gammaglobulin) were higher in FcγRIIb-/- mice compared to wild-type. Accordingly, HP infection also accelerated the severity of lupus as determined by proteinuria, serum creatinine, serum cytokines, renal histology, and renal immune complex deposition. Although HP increased serum cytokines in both wild-type and FcγRIIb-/- mice, the levels were higher in FcγRIIb-/- mice. As such, HP also increased spleen weight and induced several splenic immune cells responsible for antibody productions (activated B cell, plasma cell and follicular helper T cell) in FcγRIIb-/- mice, but not in wild-type. These data describe the different systemic responses against localized HP infection from diverse host genetic background. In conclusion, the mutual interactions between HP and lupus manifestations of FcγRIIb-/-mice were demonstrated in this study. With the prominent immune responses from the loss of inhibitory signalling in FcγRIIb-/- mice, HP infection in these mice induced intense chronic inflammation, increased antibody production, and enhanced lupus severity. Thus, the increased systemic inflammatory responses due to localized HP inducing gastritis in some patients with lupus may enhance lupus progression. More studies are needed.